Entrepreneurial skills and its relationship with MSMES performance - Macedo, Karieli Belli de Mello; Hahn, Ivanete Schneider; Bianchi, Julia; Ogoshi, Rosana Claudio Silva (Revista de Administração da UFSM, 2020)
Purpose – This research aimed to study the relationship between entrepreneurial skills and MSMEs (Micro Small and Medium Enterprises) performance. Design/methodology/approach – A quantitative and descriptive research was conducted, operationalized through a survey with 47 MSMEs entrepreneurs. Findings – (1) Most responding entrepreneurs seek opportunities, take calculated risks, and often demand quality and efficiency in their activities within the company. It can also be noted that they always pointed to being persistent, committed and seeking information. They also demonstrated that they often set goals, plan and monitor, maintain contact with their networks, are independent and self-confident; (2) the majority (60.4%) are in high sales growth, 14.6% found to be very profitable and 68.7% have medium to high profitability, 68.8% of them have good market share - so, companies show a positive perception of performance; (3) it was possible to verify that there is a relationship between entrepreneurial skills and the performance of MSMEs. Research implications – even young adults are a representation of future main leaders there is no significant difference between their entrepreneurial skills with other MSMEs owners. Moreover, in the set power, in our study just Persuasion and Network showed relation with performance, even in previous study independence and self-confidence had a relationship with performance. Originality/value: It was possible to conclude that the systematic planning and monitoring and the persuasion and network of contacts are the decisive entrepreneurial characteristics in the performance of the MSMEs.